Health Functionalities of Betaine in Patients With Homocystinuria - Truitt, Chelsea; Hoff, Wouter D.; Deole, Ratnakar (Frontiers in Nutrition, 2021)
Homocystinuria is a medical condition that can have widespread and harmful effects on multiple organ systems within the body. This disease is caused by a deficiency in one of the enzymes involved in the methionine metabolism pathway. One example would be a deficiency in cystathionine-β-synthase (CBS), which is seen in classical homocystinuria. A deficiency in CBS can lead to elevated levels of homocysteine and possible depletion of methionine and/or cysteine. There are several different treatment options for patients with this condition, one of which is the administration of the drug betaine. Here we review the use of betaine to decrease these elevated levels of homocysteine back to within normal ranges. Published literature indicates that the use of this choline derivative is most beneficial to patients who are either not compliant with the recommended low methionine and low protein diet or wish to consume a less restricted diet.